1985
DOI: 10.1021/bi00323a014
|View full text |Cite
|
Sign up to set email alerts
|

Use of secondary isotope effects and varying pH to investigate the mode of binding of inhibitory amino aldehydes by leucine aminopeptidase

Abstract: Ki values for leucine aldehyde, a competitive inhibitor of leucine aminopeptidase, vary with pH in a manner compatible with binding of uncharged inhibitor. The pH dependence of kcat/Km suggests likewise that the substrate leucine p-nitroanilide is productively bound as the uncharged species. Comparison of pKa values of the model compounds aminoacetone and aminoacetal indicates that the equilibrium constant for hydration of amino aldehydes is reduced by a factor of about 2 when a proton is lost from the alpha-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…However the pH optima for aminopeptidase activity in control leaf extracts was found to be neutral (pH 7.0). Recent X-ray crystallographic studies have suggested that the alkaline pH optima may reflect the need for the substrate's N-terminus to be in an unprotonated state to facilitate interaction with the hydrophobic catalytic core of enzyme [26,27]. Interestingly our findings suggest that pigeonpea inducible aminopeptidase may have alkaline pH optima since pH optima for enzyme activity was alkaline in the leaf extracts of treated plants.…”
Section: Discussionmentioning
confidence: 52%
“…However the pH optima for aminopeptidase activity in control leaf extracts was found to be neutral (pH 7.0). Recent X-ray crystallographic studies have suggested that the alkaline pH optima may reflect the need for the substrate's N-terminus to be in an unprotonated state to facilitate interaction with the hydrophobic catalytic core of enzyme [26,27]. Interestingly our findings suggest that pigeonpea inducible aminopeptidase may have alkaline pH optima since pH optima for enzyme activity was alkaline in the leaf extracts of treated plants.…”
Section: Discussionmentioning
confidence: 52%
“…Further biochemical characterization of the porcine LAP, E. coli PepA and tomato LAP‐A showed that all three LAPs had high temperature and alkaline pH optima. Recent X‐ray crystallographic studies have suggested that the alkaline pH optima may reflect the need for the substrate’s N‐terminus to be in an unprotonated state to facilitate interaction with the hydrophobic catalytic core of LAP [13,51]. It is also possible that the tomato LAP‐A’s alkaline pH optimum may be related to its site of action within the plant cell or its role in plant defense.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds containing the aldehyde component often serve as very effective inhibitors of proteolytic enzymes such as elastase (26), papain (27)(28)(29), chymotrypsin (30), amidase (31), asparaginase (32), leucine aminopeptidase (33,34), and the serine protease SGPA from Streptomyces griseus (35). The enhanced electrophilicity at the carbonyl carbon of the aldehyde invites a fourth saturating ligand, such as a water molecule, exemplified by aldehyde-hydrate equilibria in aqueous solution.…”
mentioning
confidence: 99%